Licensing of Building Construction That is Not in Accordance With the Provisions of Government Regulations on the Implementing Regulations of Law Number 28 Of 2002 Concerning Buildings in the City Of Cilegon - Nadin, Natasya Lia; Fathullah, Fathullah; Nurtresna, Robby (SEAN Institute, 2025)
In accordance with Government Regulation (PP) No. 16 of 2021 concerning Building Construction, the government has changed the provisions of the Building Construction Permit (IMB) to the Building Construction Approval (PBG). Building Construction Approval (PBG) is a permit given to building owners to build new, expand, reduce or maintain buildings in accordance with building technical standards. In this case, the problem that arises is the inconsistency of building construction permits in Cilegon City. The problem is that there are several buildings in Cilegon City that do not comply with their function, because at the beginning of land registration, the building was designated as a residential building or residence, over time the building changed function as a place of business. The research method used is empirical with a normative approach. The data sources used are primary data and secondary data. Primary data is data obtained from the parties related and involved in this study, namely the Cilegon City Public Works and Spatial Planning Service, the Cilegon City Investment and One-Stop Licensing Service (DPMPTSP), and the Cilegon City BAPPEDALITBANG. While secondary data is data obtained from literature studies. Based on the results of research related to violations committed by building owners if the building has been built without a Building Permit (PBG), the government has the right to direct the building owner to immediately take care of the Certificate of Functional Worthiness (SLF) to obtain a Building Permit (PBG). If the building owner builds a building in a place where building construction is prohibited, the government will demolish it.